PENGEMBANGAN BAHAN AJAR FLIPBOOK BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PERANAN MASYARAKAT DALAM RANTAI EKONOMI DI SMP LABSCHOOL UNESA 1 SURABAYA - Ajeng Sofia Zakiatik; Nurul Hasanah; Nuansa Bayu Segara; Asnimawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
IPS lessons at secondary school level still rely heavily on traditional teaching materials such as LKS and printed books, resulting in lessons that are monotonous and less interactive, and which do not connect the material with the real-life experiences of students. This causes students to be less involved in understanding the role of society in the economic chain. This study aims to determine the suitability and response of students to the flipbook teaching material based on Contextual Teaching and Learning (CTL) for the topic 'The Role of Society in the Economic Chain' at SMP Labschool Unesa 1 Surabaya. The study used the Research and Development (R&D) method with the 4-D model, which includes the define, design, develop, and disseminate stages. Data was collected using observation, interviews, expert validation (media and subject matter experts), and a questionnaire for teachers and students. The data were analysed using descriptive qualitative and descriptive quantitative methods with a Likert scale. The results of the study showed that the flipbook-based CTL teaching material received an average percentage rating of 88% from the media expert and 95% from the subject expert, both in the 'very suitable' category. Additionally, the response of the students in the small-scale trial was 81% with a very good rating, while the response of the students in the large-scale trial and the teachers was 98% with a very good rating. The conclusion of this study is that the CTL-based flipbook teaching material meets the criteria for suitability and can be used as a teaching material for the 'Peranan Masyarakat Dalam Rantai Ekonomi' (The Role of Society in the Economic Chain) subject. It is recommended that future research expands the development of teaching materials to include other aspects of the curriculum and that they are tested on a larger scale to assess their effectiveness.